2018
DOI: 10.1182/blood-2018-01-827964
|View full text |Cite
|
Sign up to set email alerts
|

Bcor insufficiency promotes initiation and progression of myelodysplastic syndrome

Abstract: Abstract BCOR, encoding BCL-6 corepressor (BCOR), is X-linked and targeted by somatic mutations in various hematological malignancies including myelodysplastic syndrome (MDS). We previously reported that mice lacking Bcor exon 4 (BcorΔE4/y) in the hematopoietic compartment developed NOTCH-dependent acute T-cell lymphoblastic leukemia (T-ALL). Here, we analyzed mice lacking Bcor exons 9 and 10 (BcorΔE9-10/y), which express a carboxyl-terminal truncated BCOR that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 31 publications
8
69
0
2
Order By: Relevance
“…The type of myeloid neoplasm developing in Bcor-deficient mouse may vary depending on the co-occurring genetic lesions. For example, compound mice carrying concurrent full deletion of Tet2 develop lethal MDS [19] whilst Bcor loss cooperates with Kras G12D to drive AML [17].…”
Section: Introductionmentioning
confidence: 99%
“…The type of myeloid neoplasm developing in Bcor-deficient mouse may vary depending on the co-occurring genetic lesions. For example, compound mice carrying concurrent full deletion of Tet2 develop lethal MDS [19] whilst Bcor loss cooperates with Kras G12D to drive AML [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tara et al demonstrated that Bcor mutation which lacks interaction with non-canonical PRC1.1 containing PCGF1 and promotes MDS/MPN development in mouse model [71]. This Bcor mutant mouse showed substantial derepression of Hoxa7 and Hoxa9 gene via reduction of H2AK119ub at the Hoxa7 and Hoxa9 gene loci.…”
Section: Regulation Of Hoxa Gene Expression By H2ak119ub Modificationmentioning
confidence: 99%
“…The depletion of both Runx1 and Pcgf1 resulted in the maintenance of proliferation of hematopoietic progenitor cells and perturbed their differentiation because of increased expression of posterior Hoxa cluster genes such as Hoxa9 [21]. Similarly, myeloid cells in mice lacking Bcor exons 9 and 10, which generates a truncated form of Bcor that does not bind Pcgf1, have a higher proliferative capacity, which results in myeloid-biased hematopoiesis [22,23]. Bcor-deficient HSCs have increased expression of Cebp family genes in MPPs and sustained expression of posterior Hoxa cluster genes in myeloid progenitors [23].…”
Section: Prc2mentioning
confidence: 99%
“…Similarly, myeloid cells in mice lacking Bcor exons 9 and 10, which generates a truncated form of Bcor that does not bind Pcgf1, have a higher proliferative capacity, which results in myeloid-biased hematopoiesis [22,23]. Bcor-deficient HSCs have increased expression of Cebp family genes in MPPs and sustained expression of posterior Hoxa cluster genes in myeloid progenitors [23]. These findings indicate that PCR1.1 negatively regulates critical transcriptional regulator genes, such as Cebp, and Hoxa9, to restrict the proliferation and differentiation of myeloid progenitor cells.…”
Section: Prc2mentioning
confidence: 99%
See 1 more Smart Citation